Bazzania Gray (Lepidoziaceae, Marchantiophyta) in Central Java, Indonesia - LILIH KHOTIMPERWATI; RINA SRI KASIAMDARI; SANTOSA SANTOSA; BUDI SETIADI DARYONO (Society for Indonesian Biodiversity, 2018)
Khotimperwati L, Kasiamdari RS, Santosa, Daryono BS. 2018. Bazzania Gray (Lepidoziaceae, Marchantiophyta) in Central Java, Indonesia. Biodiversitas 19: 875-887. Bazzania has the largest species of the family Lepidoziaceae (Marchantiophyta). This genus is abundant in the moist montane forest. Diversity of Bazzania in Java insufficiently reported, especially publications about its diversity in Central Java have never been reported. Therefore this study aimed to explore the diversity of Bazzania in Central Java. Studies of the Bazzania were based on the specimens collected from three mountains in Central Java, i.e. Mt. Lawu, Mt. Ungaran and Mt. Slamet. The observation in the laboratory was done based on the morphological and anatomical feature of the stem, lateral leaf, underleaves (amphigastria) and microphyll. Identification of the species used the existing literature that contains key identification, description or illustration of the Bazzania. Eleven species of Bazzania were identified from Central Java, namely Bazzania calcarata, B. japonica, B. javanica, B. pectinata, B. praerupta, B. serpentina, B. spiralis, B. tridens, B. fauriana, B. perfalcata and B. succulenta. Three new record species, namely B. fauriana, B. perfalcata and B. succulenta are reported for Java. This result is the first report of Bazzania in part of Central Java.